Transformation Educational Goals into Performance Indicators in Lithuanian and International Education Policy - Želvys, Rimantas; Dukynaitė, Rita; Vaitekaitis, Jogaila; Jakaitienė, Audronė (Acta Paedagogica Vilnensia, 2020)
This article deals with the problem of the multiplicity of educational goals and their reduction into measurable indicators. The paper debates whether an increasingly predominant student performance-centered approach, which is mainly limited to PISA findings, is a manifestation of a changing global educational paradigm; what concept of educational purposes prevails in today’s world; wh